Schistosoma Japonicum Infection of the Ureter and Bladder: A Case Report and Literature Review - Rongchen Wang, MM, Li Qiu, MD (Advanced Ultrasound in Diagnosis and Therapy, 2023)
Schistosoma japonicum causes intestinal schistosomiasis, which affects mainly the rectum and sigmoid colon but rarely the urinary tract. Here we report a rare case of S. japonicum infection of the bladder and ureter, and describe its clinical features and imaging findings. We also put this case in perspective with the literature on S. japonicum infections in humans.